Strategi Pemasaran Efektif terhadap Keputusan Pembelian Teh Break di Kota Lamongan - Imtinan Widhah Kumala; Bayu Malikhul Askhar; Mohamad Fahmi Yusuf; M Adhitya Nugraha Pratama; Fauziah Maulida (Jurnal Syntax Admiration, 2024)
This study aims to analyze the influence of customer satisfaction, strategic location, and promotion on consumer purchasing decisions in teh break businesses in Lamongan. The research method employed is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), with data collected through a survey of 100 respondents selected using the purposive sampling technique. The results reveal that all independent variables, namely customer satisfaction, strategic location, and promotion, positively and significantly affect consumer purchasing decisions. Strategic location has the greatest influence (β = 0.412; t-statistic = 5.673), followed by customer satisfaction (β = 0.321; t-statistic = 4.256) and promotion (β = 0.287; t-statistic = 3.892). The research model explains 65.2% of the variance in purchasing decisions (R² = 0.652). This study highlights the importance of strategic location, customer satisfaction, and promotion in shaping purchasing decisions. The findings are expected to serve as a reference for teh break business owners in formulating more effective marketing strategies.